Pengaruh Model Pembelajaran Problem Based Learning Berkonteks Socio Scientific Issues Terhadap Kemampuan Literasi Sains Siswa pada Materi Asam Basa - Nur Azizah, Dinda; Irwandi, Dedi; Saridewi, Nanda (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
This research is motivated because the low scientific literacy of Indonesian students based on PISA. The purpose of this research in order to understand the influence of a Problem Based Learning (PBL) using Socio Scientific Issues (SSI) learning context on students’ scientific literacy abilities. This research was conducted at SMAN 28 Kabupaten. The method used in this study was quasi experimental design, with research design nonequivalent control group. Population of this study were all the student of XI science classes. The data were collected through essay test consisting of 13 items related to scientific literacy abilities. The data obtained were analyze by independent sample t-test. The test result of independent sample t-test show sig < 0,05 at significance 5%, then H1 is accepted. The result indicated that Problem Based Learning (PBL) using Socio Scientific Issues (SSI) learning context had a significance effect on students’ scientific literacy abilities in acid base topic. Keywords : Problem Based Learning (PBL), Socio Scientific Issues (SSI), Scientific Literacy Abilities, Acid Base